Anti-Pseudomonas aeruginosa activity of hemlock (Conium maculatum, Apiaceae) essential oil. Issue 23 (2nd December 2019) - Di Napoli, Michela; Varcamonti, Mario; Basile, Adriana; Bruno, Maurizio; Maggi, Filippo; Zanfardino, Anna
Abstract: Conium maculatum is a nitrophilous weed belonging to the Apiaceae family and occurring in hedgerows, pastures, waste ground, along rivers and roadsides. Little is known on the chemistry and bioactivity of other secondary metabolites occurring in the plant. In the present work, we have analysed the chemical composition and antimicrobial activity of the essential oils hydrodistilled from leaves and inflorescenes of C. maculatum growing in Sicily, Italy. The composition of essential oils was achieved by gas chromatography-mass spectrometry (GC-MS) analysis, whereas the inhibitory effects on the growth of two Gram negative strains, namely Escherichia coli and Pseudomonas aeruginosa were assessed by two different analysis. The essential oils exhibited different chemical profiles (1-butylpiperidine and myrcene in the inflorescenes), (mostly ( E )-caryophyllene in the leaves). The latter oil was particularly active in inhibiting the growth of P. aeruginosa . These results shed light on the possible application of hemlock essential oils as antimicrobial agents. Abstract :